Tsuji–Wacker Oxidation of Terminal Olefins using a Palladium–Carbon Nanotube Nanohybrid. Issue 15 (17th July 2015) - Donck, Simon; Gravel, Edmond; Shah, Nimesh; Jawale, Dhanaji V.; Doris, Eric; Namboothiri, Irishi N. N.
Abstract Palladium nanoparticles supported on carbon nanotubes were used in the Tsuji–Wacker oxidation. The palladium‐based nanohybrid was found to be very active in combination with cuprous chloride for the selective oxidation of terminal olefins into methyl ketones. The co‐catalytic system operates under very mild and sustainable conditions (room temperature, atmospheric pressure, low catalyst loading), as opposed to previously reported catalysts, and can be recycled without any loss in activity.